New records and noteworthy data of plants, algae and fungi in SE Europe and adjacent regions, 16 - Gordana Tomović; Marko S. Sabovljević; Vladan Djordjević; Svetlana Krdžić; Marjan Niketić; Sanja Šovran; Ana Knežević; Péter Szűcs; Dimitar Stoykov; Miruna-Maria Ștefănuț; Danijela Vidaković; Jelena Krizmanić; et al. (Botanica Serbica, 2024)
This paper presents new records and noteworthy data on the following taxa in SE Europe and adjacent regions: diatoms Discostella asterocostata and Stephanodiscus hantzschii f. tenuis, red alga Bangia atropurpurea, green alga Ulva pilifera, saprotrophic fungi Didymella vitalbina and Phragmotrichum rivoclarinum, mosses Buxbaumia aphylla, Sphagnum divinum, and Tortella fasciculata, monocots Anacamptis × nicodemi, Epipactis palustris, Epipogium aphyllum, and Gymnadenia frivaldii and dicots Androsace lactea, Drosera rotundifolia, Potentilla montenegrina, and Tozzia alpina subsp. carpathica are given within SE Europe and adjacent regions.